2015
DOI: 10.1177/0333102415598757
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of pentraxin-3 and other inflammatory biomarkers in migraine: Association with migraine characteristics

Abstract: PTX-3 and fibrinogen exhibit different serum levels in patients undergoing a migraine attack compared with the interictal group and the controls. Participants with longer attacks and disease durations have lower serum levels of PTX-3, suggesting that inflammatory processes change along with disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Additionally, it has been reported that the levels of acute phase protein increased in a variety of neurodegenerative diseases [36, 37]. For instance, Lee et al have observed high plasma PTX3 levels in idiopathic PD patients and found significant correlation between the PTX3 levels and daily life activities and motor functions [38].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that the levels of acute phase protein increased in a variety of neurodegenerative diseases [36, 37]. For instance, Lee et al have observed high plasma PTX3 levels in idiopathic PD patients and found significant correlation between the PTX3 levels and daily life activities and motor functions [38].…”
Section: Discussionmentioning
confidence: 99%
“…Pentraxin 3 (PTX3) is a member of the long pentraxin family that acts as an acute phase inflammatory glycoprotein [10]. Two studies have demonstrated higher plasma levels of PTX3 in migraine patients during attacks when compared to interictal periods [11] or healthy controls [12]. Plasma levels of soluble tumour necrosis factor-like weak inducer of apoptosis (sTWEAK) have been analysed as potential biomarkers of cardiovascular disease and endothelial dysfunction in vascular [13][14][15] and non-vascular diseases [16].…”
Section: Introductionmentioning
confidence: 99%
“…A critical study by Ceylan et al investigating inflammatory markers in serum in migraine patients found higher levels of fibrinogen and pentraxin-3 (PTX-3) in migraine patients suffering acute attacks as compared to those in healthy control patients. However, the same study found no significant difference in C-reactive protein (CRP) levels between the patient groups within the attack and interictal period [24]. Remarkably, they found higher serum levels of fibrinogen and PTX-3 in migraine attack patients compared with patients during the interictal period [24].…”
Section: The Results Of the Comparisons Of Nlr Between The Patient Grmentioning
confidence: 88%
“…However, the same study found no significant difference in C-reactive protein (CRP) levels between the patient groups within the attack and interictal period [24]. Remarkably, they found higher serum levels of fibrinogen and PTX-3 in migraine attack patients compared with patients during the interictal period [24]. Among the inflammatory markers used in the clinical practice, WBC count is a crucial one used also widely in scientific researches.…”
Section: The Results Of the Comparisons Of Nlr Between The Patient Grmentioning
confidence: 93%
See 1 more Smart Citation